If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 18x + -2 = 19x + 17 + -4x Reorder the terms: 6 + -2 + 18x = 19x + 17 + -4x Combine like terms: 6 + -2 = 4 4 + 18x = 19x + 17 + -4x Reorder the terms: 4 + 18x = 17 + 19x + -4x Combine like terms: 19x + -4x = 15x 4 + 18x = 17 + 15x Solving 4 + 18x = 17 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 18x + -15x = 17 + 15x + -15x Combine like terms: 18x + -15x = 3x 4 + 3x = 17 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + 3x = 17 + 0 4 + 3x = 17 Add '-4' to each side of the equation. 4 + -4 + 3x = 17 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 17 + -4 3x = 17 + -4 Combine like terms: 17 + -4 = 13 3x = 13 Divide each side by '3'. x = 4.333333333 Simplifying x = 4.333333333
| 5m+5m=90 | | y/19=-17 | | (-5+7i)(8-9i)= | | 2n=-18 | | -44x=-88 | | p^2+2p=48 | | 49=q+12 | | 80=a+75 | | x/6-46=-30 | | X/4-y/5 | | -84=28x | | -9(-25.2)+5y=-45 | | C-3/3-C | | 3/4x+5/7x | | 8X(6)=12 | | 1.6q-1.9-4.8q=4.2q-3.8 | | 8X(6)=10 | | 420/14 | | (2x^3-6x^2+5x)-(7x^2+4x+8)= | | 1/4/420 | | 12+(30-5x)=42 | | 15/9+92/5= | | 420/1/14 | | 4v^4/2v^2-14v^3/2v^2 | | (2x^2y+2xy+2x^2)dx+(2x^3y+2x^2+2xy)dy=0 | | 7z=9 | | x+(4x/2-3)=12/(x-3) | | 5x+y=236 | | 5xY=236 | | 10-3c=4 | | d/3-d-1/6=7/6 | | 8(x-1)=4x+7 |